“Living in a Communal Garden” Associated with Well-Being While Reducing Urban Sprawl by 40%: A Mixed-Methods Cross-Sectional Study - Anderson, Jamie (Frontiers in Public Health, 2015)
Background The extent to which novel land-efficient neighborhood design can promote key health behaviors is examined, concentrating on communal outdoor space provision (COSP). Objectives To test whether a neighborhood (Accordia) with a higher ratio of communal to private outdoor space is associated with higher levels of resident’s (a) self-reported local health behaviors and (b) observed engagement in local health behaviors, compared to a matched neighborhood with lower proportion of COSP. Methods Health behaviors were examined via direct observation and postal survey. Bespoke observation codes and survey items represented key well-being behaviors including “connecting,” “keeping active,” “taking notice,” “keep learning,” and “giving.” The questionnaire was validated using psychometric analyses and observed behaviors were mapped in real-time. Results General pursuit of health behaviors was very similar in both areas but Accordia residents reported substantially greater levels of local activity. Validated testing of survey dataset (n = 256) showed support for a stronger Attitude to Neighborhood Life (connecting and giving locally) in Accordia and partial support of greater physical activity. Analyses of the behavior observation dataset (n = 7,298) support the self-reported findings. Mapped observations revealed a proliferation of activity within Accordia’s innovative outdoor hard spaces. Conclusion Representation is limited to upper-middle class UK groups. However, Accordia was found to promote health behaviors compared a traditional neighborhood that demands considerably more land area. The positive role of home zone streets, hard-standing and semi-civic space highlights the principle of quality as well as quantity. The findings should be considered as part of three forthcoming locally led UK garden cities, to be built before 2020.